(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
To reflect the specifics of the use of new approaches to management in the process of continuous development of structural and organizational changes in enterprises. Processes in enterprises that carry out the processes of production and distribution among consumers, considered as consumers and producers of material, energy, financial and information flows. The main goal is to improve the algorithmic model of information and analytical support of the process of resource management creation and development of information management system for